ATP7A delivers copper to the lysyl oxidase family of enzymes and promotes tumorigenesis and metastasis - Shanbhag, Vinit (Proc Natl Acad Sci U S A, 2019)
Lysyl oxidase (LOX) and LOX-like (LOXL) proteins are copper-dependent metalloenzymes with well-documented roles in tumor metastasis and fibrotic diseases. The mechanism by which copper is delivered to these enzymes is poorly understood. In this study, we demonstrate that the copper transporter ATP7A is necessary for the activity of LOX and LOXL enzymes. Silencing of ATP7A inhibited LOX activity in the 4T1 mammary carcinoma cell line, resulting in a loss of LOX-dependent mechanisms of metastasis, including the phosphorylation of focal adhesion kinase and myeloid cell recruitment to the lungs, in an orthotopic mouse model of breast cancer. ATP7A silencing was also found to attenuate LOX activity and metastasis of Lewis lung carcinoma cells in mice. Meta-analysis of breast cancer patients found that high ATP7A expression was significantly correlated with reduced survival. Taken together, these results identify ATP7A as a therapeutic target for blocking LOX- and LOXL-dependent malignancies.